Anda di halaman 1dari 4

LIMIT

Tentukan nilai limit berikut:


( x3 1) ( x3 + 1)
x6 1
= lim
=2
1. lim 3
x 1 x 1
x1
x3 1
2x2 + x 6
x 2 4
8 x + 3 4 x

2. lim

( x + 2)(2 x 3)
= lim 4
.
x 2
8 x + 3 4 x
= lim

x 2

= lim

8 x 3 4 x
4
8 x 3 4 x

( x + 2)(2 x 3)( 4 8 x 3 4 x )
8 x 3 16 x 2

8 x + 3 16 x 2
8 x + 3 16 x 2

( x + 2)(2 x 3)( 4 8 x 3 4 x )( 8 x + 3 16 x 2 )
8 x 3 256 x 4

x 2

( x + 2)(2 x 3)( 4 8 x 3 4 x )( 8 x + 3 16 x 2 )
= lim
x 2
8 x 4 x 3 4 x
( x + 2)(2 x 3)( 4 8 x 3 4 x )( 8 x + 3 16 x 2 )
= lim
.
x 2
4 x( 3 4 x + 2)

16 x 2 2 3 4 x + 4

16 x 2 2 3 4 x + 4

( x + 2)(2 x 3)( 4 8 x 3 4 x )( 8 x + 3 16 x 2 )( 3 16 x 2 2 3 4 x + 4)
x 2
4 x(4 x + 8)

= lim
= lim

( x + 2) (2 x 3)( 4 8 x 3 4 x )( 8 x + 3 16 x 2 )( 3 16 x 2 2 3 4 x + 4)

x 2

7.4.8.12
= 84
16. 2

( x3 27)( x 3 + 27)
3. lim
3
x 3
4 x 3 12

16 x ( x + 2)

( x 3)( x 2 + 3x + 9)( x3 + 27) 3 16 x 2 + 3 48 x + 3 144


= lim
.
3
3
x 3
4 x 3 12
16 x 2 + 3 48 x + 3 144
( x 3)( x 2 + 3x + 9)( x3 + 27)( 3 16 x 2 + 3 48 x + 3 144)
x 3
4 x 12

= lim
= lim

( x 3) ( x 2 + 3x + 9)( x3 + 27)( 3 16 x 2 + 3 48 x + 3 144)


4 ( x 3)

x 3

27.54.3 3 144 2187 3


=
=
144
4
2
(2 3 x )( 4 2 x + 2)
4. lim
x 8 4
( 2 x 2)(2 + 3 x )
(2 3 x )( 4 2 x + 2) 4 + 2 3 x + 3 x 2
= lim 4
.
.
x 8 ( 2 x 2)(2 + 3 x )
4 + 2 3 x + 3 x2
= lim
x 8

= lim
x 8

= lim
x 8

(8 x)( 4 2 x + 2)( 4 2 x + 2)
( 2 x 4)(2 + 3 x )(4 + 2 3 x + 3 x 2 )

(8 x)( 4 2 x + 2)( 4 2 x + 2)( 2 x + 4)


(2 x 16)(2 + 3 x )(4 + 2 3 x + 3 x 2 )
( x 8) ( 4 2 x + 2)( 4 2 x + 2)( 2 x + 4)
2 ( x 8) (2 + 3 x )(4 + 2 3 x + 3 x 2 )

4.4.8
16
4
= =
2.4.12
12
3

5. lim
x 1

x3 3 x
x5 ( 4 x3 x 2 )

4
4

2x + 2
2x + 2

2x + 4
2x + 4

= lim
x 1

= lim
x 1

= lim
x 1

= lim
x 1

= lim
x 1

x3 3 x
x5 ( 4 x3 x 2 )

x6 + x3 3 x + 3 x 2

x6 + x3 3 x + 3 x 2

( x9 x)( 4 x3 + x 2 )
x5 ( x 3 x 4 )( x 6 + x 3 3 x + 3 x 2 )

x3 + x 2

x3 + x 2

x3 + x 4
x3 + x 4

( x9 x)( 4 x3 + x 2 )( x 3 + x 4 )
x5 ( x3 x8 )( x 6 + x 3 3 x + 3 x 2 )
x( x8 1)( 4 x 3 + x 2 )( x 3 + x 4 )
x8 ( x5 1)( x 6 + x3 3 x + 3 x 2 )
x ( x 1) ( x 7 + x 6 + x 5 + x 4 + x 3 + x 2 + x + 1)( 4 x 3 + x 2 )( x 3 + x 4 )
x8 ( x 1) ( x 4 + x 3 + x 2 + x + 1)( x 6 + x 3 3 x + 3 x 2 )

1.8.2.2
32
=
1.5.3
15

6. lim
x 1

( x 6 4 x3 + x + 2)( x 6 2 x 3 + 1)
( x 1)( x 2 1)(1 + 3 x + 3 x 2 )

= lim
x 1

( x 1)( x5 + x 4 + x3 3x 2 3 x 2)( x 3 1) 2
( x 1)( x 1)( x + 1)(1 + 3 x + 3 x 2 )

x +1 1 3 x
.
x +1 1 3 x

( x 1)( x5 + x 4 + x3 3x 2 3 x 2){( x 1)( x 2 + x + 1)}2 ( x + 1)(1 3 x )


x 1
( x 1)( x 1)( x + 1)(1 x)

= lim
= lim

( x 1) ( x 5 + x 4 + x3 3 x 2 3 x 2) ( x 1) 2 ( x 2 + x + 1) 2 ( x + 1)(1 3 x )

x 1

( x 1) ( x 1) ( x + 1) ( x 1)

5.9.2.0
=0
2

x2 + 2 x + 1 x2 + 2 x + 1
x
x2 + 2x + 1

7. lim
=

1+ 0 + 0 0 + 0 + 0
=1
1+ 0 + 0

Tentukan Nilai a dan b jika:


3 ax + b 4
=
x 2 4
8x 2 x 3

8. lim

3 2a + b = 0
9 = 2a + b
b = 9 2a
3 ax + 9 2a 4 8 x + 2 x 3 + ax + 9 2a 4
.4
.
=
4
x 2
8x 2x
8 x + 2 x 3 + ax + 9 2a 3

lim

(9 a ( x 2) 9)( 4 8 x + 2 x ) 8 x + 2 x 4
lim
.
=
x 2
( 8 x 2 x)(3 + a( x 2) + 9) 8 x + 2 x 3
lim
x 2

a ( x 2) ( 4 8 x + 2 x )( 8 x + 2 x)
4 x ( x 2) (3 + a ( x 2) + 9)

4
3

a.4.8 4
=
8.6 3
a=2
b = 9 2a = 5
( x 1)(bx + 1) + 3 x 1
=1
x 1
x 2 + 2ax + a 2

9. lim

1 + 2a + a 2 = 0
(a + 1) 2 = 0
a = 1
( x 1)(bx + 1) + 3 x 1 3 x 2 + 3 x + 1
lim
.
=1
3 2
x 1
x2 2 x + 1
x + 3 x +1
lim
x 1

lim
x 1

( x 1)(bx + 1)( 3 x 2 + 3 x + 1) + x 1
( x 1)( x 1)( 3 x 2 + 3 x + 1)
( x 1) {(bx + 1)( 3 x 2 + 3 x + 1) + 1}
( x 1) ( x 1)( x + x + 1)

(b + 1).3
=1
0.3
b = 1

=1

=1

Anda mungkin juga menyukai